On not starting with a blank page: Russian classics as a palimpsest for writers 1980-2020 - Parthé, Kathleen; Maslennikova, Anna (Poljarnyj vestnik, 2024)
Between 1980 and 2020 Russia’s writers experienced profound changes in their personal and professional lives, as history presented yet another tabula rasa, but when sitting down to write (and despite the advice of Alexander Genis), writers did not see a blank page, but one covered with existing titles, characters, plots, settings, fixed expressions (krylatye vyrazheniia) and the reflections and shadows, literal and figurative, of earlier works. Unlike what Vladimir Kantor describes as Soviet-era erzatsliteratura (15) the classics offered high drama and low farce, the deepest as well as the most charmingly superficial protagonists, unforgettable flights of language, and urgent topics of the day presented against a backdrop of eternal spiritual and moral questions. For those writers wishing to circumvent the klassiki, while still linking themselves to Russia’s past, there were pre-modern religious and folk narratives, lengthening the canon’s timeline while appearing to free it from western influences or imperial ambitions. After tracing how the reputation of Russia’s klassiki and their desirability as a model changed over time, this paper will offer a descriptive survey of how specific characteristics of predecessors’ works reappeared during this four-decade stretch, with a special focus on the profound reaction to Nabokov. Our aim is to go beyond the concept of tvorcheskaia preemstvennost’ (creative continuity), which allows for broad observations, for example, about the “Gogolian” or “Chekhovian” atmosphere of a given work. Seeing how much material was creatively redeployed, we will consider what contemporary readers need to know about ur-texts (or pre-texts) – beyond what can be found on a quick internet search – in order to appreciate works bearing the influence of past writers. Finally, we ask whether the term “Great Russian Literature” still refers to an inherited literary culture appreciated far beyond Russia’s borders, or whether now, in the 2020s, it is more closely associated with the aggressive nationalism emanating from Moscow.